Substitution of Corn Flour and Additional Palm Sugar to Cookies Characteristics - Ni Kadek Karina Sari Dewi; I Wayan Sudiarta; I Nyoman Rudianta (Warmadewa University Press, 2022)
Cookies are biscuits made from low protein flour, and have a crunchy texture. Corn flour substitute was chosen because corn flour only contains <1% gluten. The main problem faced by corn commodity lies in the low sugar content as energy. To produce cookies that have nutritional value, palm sugar is added, where the constituent sugar is simpler than granulated sugar. This study aims to determine how the effect of corn flour substitution and the addition of palm sugar on the physicochemical and organoleptic characteristics of cookies. The design used was a Completely Randomized Design (CDR) with two factors and two replications, the first factor was corn flour substitution which consisted of four levels, namely 0%, 15%, 30%, 45%. The second factor is the addition of palm sugar which consists of three levels, namely 15%, 20%, 25%. Observations were made objectively including water content, ash content, protein content, fat content, carbohydrate content, crude fiber content and color. While subjectively include, color, aroma, texture, taste and overall acceptance. The results obtained the best formulation of cookies substituted with 30% corn flour and 20% palm sugar with a water content of 6.39%, ash content of 2.45%, protein content of 10.19%, fat content of 29.90%, carbohydrate content 51.08%, and 0.09% crude fiber content. Cookies are biscuits made from low protein flour, and have a crunchy texture. Corn flour substitute was chosen because corn flour only contains <1% gluten. The main problem faced by corn commodity lies in the low sugar content as energy. To produce cookies that have nutritional value, palm sugar is added, where the constituent sugar is simpler than granulated sugar. This study aims to determine how the effect of corn flour substitution and the addition of palm sugar on the physicochemical and organoleptic characteristics of cookies. The design used was a Completely Randomized Design (CDR) with two factors and two replications, the first factor was corn flour substitution which consisted of four levels, namely 0%, 15%, 30%, 45%. The second factor is the addition of palm sugar which consists of three levels, namely 15%, 20%, 25%. Observations were made objectively including water content, ash content, protein content, fat content, carbohydrate content, crude fiber content and color. While subjectively include, color, aroma, texture, taste and overall acceptance. The results obtained the best formulation of cookies substituted with 30% corn flour and 20% palm sugar with a water content of 6.39%, ash content of 2.45%, protein content of 10.19%, fat content of 29.90%, carbohydrate content 51.08%, and 0.09% crude fiber content.